A new brand of business : Charles Coolidge Parlin, Curtis Publishing Company, and the origins of market research - Ward, Douglas B., 1961- (Temple University Press, 2010)
Charles Coolidge Parlin was considered by many to be the founder of market research. Working for the dominant Curtis Publishing Company, he revolutionized the industry by providing added value to advertisers through information about the racial, ethnic, and regional biases of readers and consumers. By maintaining contact with both businesses and customers, Parlin and Curtis publications were able to turn consumer wants into corporate profits. In A New Brand of Business, Douglas Ward provides an intriguing business history that explains how and why Curtis developed.